2011
DOI: 10.1007/s10545-011-9424-3
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between the pharmacological chaperone 1‐deoxygalactonojirimycin and the human recombinant alpha‐galactosidase A in cultured fibroblasts from patients with Fabry disease

Abstract: Fabry disease (FD) is an X-linked inherited disease due to alpha-galactosidase A (alpha-Gal A) deficiency and characterized by lysosomal storage of globotriaosylceramide (Gb3) and related neutral glycosphingolipids. Storage of these substrates results in multisystem manifestations, including renal failure, cardiomyopathy, premature myocardial infarctions, stroke, chronic neuronopathic pain, gastrointestinal disturbances, and skin angiokeratoma. Enzyme replacement therapy (ERT) with recombinant human alpha-gala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…The past decade has witnessed extraordinary innovation in the treatment of several inherited metabolic diseases with different approaches now available in pre-clinical and clinical testing, including enzyme replacement therapy (ERT), substrate reduction and haematopoietic stem cells transplantation [1]. More innovative strategies, such as pharmacological chaperone therapy and gene therapy, are under investigation for selected inherited metabolic diseases [135][136][137].…”
Section: Disease-specific Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The past decade has witnessed extraordinary innovation in the treatment of several inherited metabolic diseases with different approaches now available in pre-clinical and clinical testing, including enzyme replacement therapy (ERT), substrate reduction and haematopoietic stem cells transplantation [1]. More innovative strategies, such as pharmacological chaperone therapy and gene therapy, are under investigation for selected inherited metabolic diseases [135][136][137].…”
Section: Disease-specific Therapymentioning
confidence: 99%
“…Some studies from our group demonstrated that the pharmacological chaperones improve the efficacy of ERT with recombinant a-glucosidase in Pompe disease, and with recombinant a-galactosidase A in Fabry disease [135,137,152,153]. Improving the efficacy of ERT has great clinical relevance in Pompe disease, as it is becoming increasingly evident that a synergistic effect of these treatments may result useful in patients responding poorly to ERT, but at present there are no studies on the effects on respiratory manifestations.…”
Section: Disease-specific Therapymentioning
confidence: 99%
“…Recent studies have shown that chemical chaperones can improve the efficacy of ERT also in FD [137][138][139]. One GLA inhibitor 1-deoxgalactonojirimycin (DGJ marked as amigal by Amicus Therapeutics, Inc) is currently being studied in a phase 3 clinical trial [140].…”
Section: Emerging Treatment Strategies For Fabry Diseasementioning
confidence: 99%
“…Although pharmacological chaperone therapy (PCT) has been developed as a strategy to rescue mutant enzymes from degradation, recent studies showed that chaperones are also able to enhance physical stability and potentiate the therapeutic action of the enzymes used for ERT (40)(41)(42)(43). These studies, performed in cell systems and in the animal models of Pompe and Fabry disease, suggested a major change in the use of PCT.…”
Section: Combination Of Chaperones and Ertmentioning
confidence: 99%
“…First, the therapeutic effect is directed toward the exogenous wild-type enzyme used for ERT, it is mutationindependent, and may thus be exploited in any patient on ERT (37,41). Second, while the enhancement of endogenous defective enzymes by chaperones in most cases results in minor changes in terms of residual activity (possibly with a modest impact on patient outcome), the synergy between chaperones and ERT apparently induces, at least in cellular models, notable increases in specific activity with complete or near-complete correction of the enzymatic defect.…”
Section: Combination Of Chaperones and Ertmentioning
confidence: 99%